2022
DOI: 10.1371/journal.pone.0267897
|View full text |Cite
|
Sign up to set email alerts
|

Health insurance status and its determinants among patients with type 2 diabetes mellitus in a tertiary teaching hospital in Malaysia

Abstract: Introduction Even in a country with a tax-based healthcare financing system, health insurance can play an important role, especially in the management of chronic diseases with high disease and economic burden such as Type 2 Diabetes Mellitus (T2DM). The insurance coverage among T2DM patients in Malaysia is currently unclear. The aim of this study was to determine the insurance status of T2DM patients in public and private healthcare facilities in Malaysia, and the association between this status and patients’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…Our study also observed that health status generally was not significantly associated with OOP expenditure, perhaps indicating that Malaysia’s heavily subsidized healthcare system did confer adequate financial risk protection to the population for inpatient care ( Chua and Cheah, 2012 ). In addition, the determinants of PHI ownership status found in our study, which was not our main interest, were comparable to other studies conducted in Malaysia ( Balqis-Ali et al ., 2021 ; Al-Sanaani et al ., 2022 ; Abd Khalim et al ., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study also observed that health status generally was not significantly associated with OOP expenditure, perhaps indicating that Malaysia’s heavily subsidized healthcare system did confer adequate financial risk protection to the population for inpatient care ( Chua and Cheah, 2012 ). In addition, the determinants of PHI ownership status found in our study, which was not our main interest, were comparable to other studies conducted in Malaysia ( Balqis-Ali et al ., 2021 ; Al-Sanaani et al ., 2022 ; Abd Khalim et al ., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…This might be because self-paying DM patients may have high substantial medical expenses or financial issues. In turn, this may lead them to forego diabetic care as well as DM medication that would otherwise help them survive their conditions ( 37 ). Another possible explanation for this is that patients without medical insurance more likely skip regular medical care ( 38 ) and do not acquire better education, which may lead to low awareness of DM medication therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This finding showed that education plays an important role, as it could enlighten individuals about the importance of health insurance coverage. 13 Education also helped individuals make informed choices about health issues, including purchasing health insurance to avoid huge health expenses when they were ill. People with higher education had a higher view of the need for health insurance to deal with unexpected health problems. In contrast, people with low education were unaware of the threat caused by unforeseen health problems.…”
Section: Discussionmentioning
confidence: 99%